When Competition Corrupts : A Theoretical Analysis of Market Structure and the Incidence of Corruption - Basu, Kaushik (World Bank, Washington, DC, 2013)
The paper develops a simple model to demonstrate that, paradoxically, greater competition may exacerbate the problem of corruption. Market participants engaging in corrupt practices enjoy lower production costs -- maybe because they pay a bribe to avoid installing the environmental safeguards required by law -- such that honest players are driven out of the market when the market becomes sufficiently competitive.